DAYA TERIMA COOKIES DENGAN SUBSTITUSI LABU KUNING DAN WORTEL SEBAGAI MAKANAN SELINGAN TINGGI BETA KAROTEN - Evie Noviani, (2020)
In Indonesia, vitamin A coverage has decreased. The prevalence of vitamin A capsule coverage in children 6-59 months of 2013 by 75,5% decreased to 53,5% in 2018. Therefore, made an effort to increase vitamin A intake by making food product that contain high beta carotene content. On of the food product is cookies. In making cookies, it is necessary to use local food ingredients such as pumpkin and carrot to reduce the use of wheat flour. This study aims to develop cookies product made of pumpkin and carrot as food high in beta carotene. This study uses an experimental method with research design is a Completely Randomized Design (CRD). There are four formulations of pumpkin and carrot of pumpkin and carrot substitution comparison is F0 as control formulation, F1 30% : 30%, F2 35% : 20%, serta F3 40% : 10%. Organoleptic test analysis used the Kruskal Wallis test and continued by the Mann Whitney test. The hedonic test result showed that there were significant different in the level of color and texture liking in the four cookies formula and there were not significant different in the level of flavor and taste liking in the four cookies formula. Determination of selected formula using ranking test based on hedonic test parameters (color, texture, flavour and taste) and analysis of chemical properties (beta karoten content). The result of study showed the selected formula in pumpkin and carrot cookies was F1 has 9,26% moisture content, 1,67% ash content, 8,24% protein content, 23,36% fat content, 57,45% carbohydrate content, and 18,916 mg beta carotene content. Therefore, this product classified as a snack that has a high content of beta carotene.